Cactus ecosystem goods and services - Louhaichi, Mounir (2017)
The Cactaceae family includes about 1 600 species native to America but disseminated worldwide. Opuntia is the most widely known genus in this family and O. ficus-indica (L.) Mill. is cultivated in more than 20 countries (Nefzaoui et al., 2014). Cacti are cultivated on 2.6 million ha across the world, and mostly used for forage or fodder: in Tunisia (600 000 ha), Mexico (230 000 ha) and Algeria (150 000 ha) (Nefzaoui and Ben Salem, 2006); in South Africa (525 000 ha) and Ethiopia (355 000 ha) (Reveles Hernández et al., 2010); in Brazil (> 600 000 ha) (Torres Sales, 2010); and in southern Morocco (90 000 ha) (Anegay and Boutoba, 2010). In Argentina, the cultivated area of cactus is estimated at 10 000 ha for forage and fruit production, with syrup as a secondary product (Dubeux et al., 2013); the area cultivated with Opuntia solely for fruit production was 2 000 ha in 2003 (Ochoa, 2006).